Helicobacter pylori and T Helper Cells: Mechanisms of Immune Escape and Tolerance - Tiziana Larussa; Isabella Leone; Evelina Suraci; Maria Imeneo; Francesco Luzza (Journal of Immunology Research)
Helicobacter pylori colonizes the gastric mucosa of at least half of the human population, causing a worldwide infection that appears in early childhood and if not treated, it can persist for life. The presence of symptoms and their severity depend on bacterial components, host susceptibility, and environmental factors, which allow H. pylori to switch between commensalism and pathogenicity. H. pylori-driven interactions with the host immune system underlie the persistence of the infection in humans, since the bacterium is able to interfere with the activity of innate and adaptive immune cells, reducing the inflammatory response in its favour. Gastritis due to H. pylori results from a complex interaction between several T cell subsets. In particular, H. pylori is known to induce a T helper (Th)1/Th17 cell response-driven gastritis, whose impaired modulation caused by the bacterium is thought to sustain the ongoing inflammatory condition and the unsuccessful clearing of the infection. In this review we discuss the current findings underlying the mechanisms implemented by H. pylori to alter the T helper lymphocyte proliferation, thus facilitating the development of chronic infections and allowing the survival of the bacterium in the human host.